The Influence of Transformational Leadership Style and Emotional Intelligence on the Performance of Generation Z Employees in the Hybrid Work Era (A Study at PT Sari Mas Permai, Palembang) - Vemi Fytaloka; Dini Pratiwi (Universitas Muhammadiyah Palu, 2025)
This study aims to examine the influence of transformational leadership style and emotional intelligence on the performance of Generation Z employees in the context of hybrid work at PT Sari Mas Permai, Palembang. The post-pandemic work landscape has driven companies to adapt to flexible work systems, which require new managerial approaches in managing the younger generation of employees. This research employs a quantitative approach using a survey method involving 100 Generation Z employees working in the administration and marketing departments. The research instruments were tested for validity and reliability, then analyzed using multiple linear regression.The results show that transformational leadership style has a positive and significant effect on employee performance, with a coefficient of 0.328 and a significance value of 0.013. Meanwhile, emotional intelligence exerts a more dominant influence with a coefficient of 0.467 and a significance value of 0.000. Simultaneously, the two independent variables explain 62.4% of the variation in employee performance (R² = 0.624). These findings affirm that the combination of inspirational leadership and strong emotional abilities are key factors in enhancing the performance of Generation Z in a dynamic and digital work environment.The implications of this study highlight the importance of developing a transformative leadership model and strengthening emotional intelligence as part of human resource management strategies. Companies need to provide training and mentoring programs to foster a work culture that supports adaptation and productivity among young employees in the hybrid work era.